2016
DOI: 10.3233/jad-160307
|View full text |Cite
|
Sign up to set email alerts
|

Human ApoE ɛ2 Promotes Regulatory Mechanisms of Bioenergetic and Synaptic Function in Female Brain: A Focus on V-type H+-ATPase

Abstract: Humans possess three major isoforms of the apolipoprotein E (ApoE) gene encoded by three alleles: ApoE ε2 (ApoE2), ApoE ε3 (ApoE3), and ApoE ε4 (ApoE4). It is established that the three ApoE isoforms confer differential susceptibility to Alzheimer’s disease (AD); however, an in-depth molecular understanding of the underlying mechanisms is currently unavailable. In this study, we examined the cortical proteome differences among the three ApoE isoforms using 6-month-old female, human ApoE2, ApoE3, and ApoE4 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…The detection of these proteins in vitrified brain tissue constitutes a valuable proof-of-concept supporting the data obtained via SEM. In particular, the finding of KIF26B involved in the organization of microtubules aligns well with the tubular structures identified inside the cytoplasmic matrix of cell bodies detected in the vitrified neuronal tissue (Fig 4B) [48,49]. The notable discovery of ATP6V1F, essential for the synaptic vesicle cycle, constitutes a further clue in favor of the discovery of human neuronal cells.…”
Section: Plos Onesupporting
confidence: 77%
See 1 more Smart Citation
“…The detection of these proteins in vitrified brain tissue constitutes a valuable proof-of-concept supporting the data obtained via SEM. In particular, the finding of KIF26B involved in the organization of microtubules aligns well with the tubular structures identified inside the cytoplasmic matrix of cell bodies detected in the vitrified neuronal tissue (Fig 4B) [48,49]. The notable discovery of ATP6V1F, essential for the synaptic vesicle cycle, constitutes a further clue in favor of the discovery of human neuronal cells.…”
Section: Plos Onesupporting
confidence: 77%
“…Expressed in the brain but with a peak in cortex and cerebellum is ATP6V1F, encoding a subunit of the catalytic domain of the V-type H+-ATPase (Atp6v), a proton pump crucial for synaptic transmission that mediates the concentration of neurotransmitters into synaptic vesicles [49]. Interestingly, of the remaining three proteins isolated from the vitrified tissue, WDR13 is encoded by a highly conserved X-linked gene expressed in all brain regions, with a peak in the pituitary gland.…”
Section: Plos Onementioning
confidence: 99%
“…Consistent with the association of synaptic loss with AD, we observed a concerted downregulation of many genes that code for proteins involved in the synaptic vesicle cycle, of which key genes are regulated by EGR3 ( Figure 6). Vacuolar ATPase (V-ATPase) is an essential proton pump highly expressed on the membrane of the presynaptic vesicle, facilitates neurotransmitter concentration in synaptic vesicles, and is differentially expressed in brains of different APOE isoforms (Woody et al, 2016). The C1 subunit of V-ATPase (ATP6V1C1) is crucial to connect the ATP catalytic domain (V 1 ) to the proton-translocation domain (V 0 ) and its downregulation has implications for vesicle acidification, as well as membrane fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Gene delivery of ApoE2 markedly reduced brain amyloid pathology in an AD mouse model . Recently, a nonbiased proteomics study from our laboratory revealed that the ApoE2 brain possessed the most robust regulatory mechanisms for synaptic transmission (Woody et al, 2016). Collectively, these studies suggest that ApoE2 brains are subjected to neuroprotective mechanisms; the uncovering of which may lead to novel AD prevention and risk reduction strategies.…”
Section: Introductionmentioning
confidence: 95%
“…cells, express primarily HK2, whereas cells that rely heavily on glycolysis for energy production, such as neurons, express predominantly Hk1 (Mandarino et al, 1995;Wilson, 2003). Additionally, it has been proposed that HK1 remains associated with mitochondria to promote glycolysis whereas HK2 dynamically translocates between cytosol and mitochondria where it directs the metabolic fate of glucose between anabolic (glycogen synthesis and pentose phosphate shunt) and catabolic (glycolysis) metabolism (Wilson, 2003;John et al, 2011). To examine the functional consequence of the differential regulation of hexokinase expression by PGC-1␣, glycolytic function was evaluated in ApoE4-expressing cells transfected with PGC-1␣.…”
Section: Pgc-1␣ Overexpression Ameliorated Bioenergetic Deficits In Nmentioning
confidence: 99%